2005
DOI: 10.1080/15227950590961216
|View full text |Cite
|
Sign up to set email alerts
|

ANAPLASTIC LARGE CELL LYMPHOMA WITH ALK EXPRESSION AND PRESENCE OF THE t(2;5) TRANSLOCATION IN A 5-MONTH-OLD INFANT

Abstract: Anaplastic large cell lymphoma (ALCL) is a well-recognized subtype of non-Hodgkin lymphoma in childhood. Several series report experience with the diagnosis and management of pediatric ALCL, the average age at diagnosis being 8 to 16 years, with a reported range of 1 to 15 years. We present a case of ALCL affecting a 5-month-old infant in whom the diagnosis was confirmed by the nuclear and cytoplasmic immunohistochemical expression of ALK1, in addition to the presence of classical t(2;5)(p23;q35) translocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The reported age range in children is 1-15 years, with an average age of diagnosis at 8-10 years [2][3][4]. It is rare in infants, with only 2 confirmed cases of t(2;5) translocations [5,6]. The association of hemophagocytic syndrome (HPS) and pediatric ALCL is uncommon, with only 3 reported cases; the youngest patient was 5 years old [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The reported age range in children is 1-15 years, with an average age of diagnosis at 8-10 years [2][3][4]. It is rare in infants, with only 2 confirmed cases of t(2;5) translocations [5,6]. The association of hemophagocytic syndrome (HPS) and pediatric ALCL is uncommon, with only 3 reported cases; the youngest patient was 5 years old [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are increasing intriguing biological data regarding infants with acute leukaemia, who mostly present with unfavourable features at initial diagnosis, such as high leucocyte counts and rearrangements of the mixed lineage leukaemia gene ( MLL ), and have a worse prognosis as compared with the older children (Pui et al , 1995; Biondi et al , 2000; Pui, 2006). In contrast, systematic and thorough data are scarce regarding the incidence, clinical and biological features and outcome of infant NHL and cases have been only anecdotally described in the literature (Grümayer et al , 1988; Neth et al , 2000; Sebire et al , 2005; Kumar et al , 2007).…”
mentioning
confidence: 99%
“…Barak et al 3 reported a 2-month-old female with disseminated ALCL and Onciu et al 4 reported a 9-month-old female with ALCL and leukemic manifestations; however, both these cases succumbed to sepsis during the chemotherapy. Sebire et al 5 reported a 5-month-old ALCL patient who relapsed on LMB 96 protocol, and achieved complete response through salvage chemotherapy.…”
Section: A Success Story Of An Infantile Anaplastic Large Cell Lympho...mentioning
confidence: 99%